Genome evolution through polyploidy: Enhancing plant stress resilience in agriculture - Patrick P. Edger; Melanie J. A. Body; Sonia De Donno; Adrian E. Platts; Jianrong Wang; Jiming Jiang (Proceedings of the National Academy of Sciences, 2026)
Polyploidy, also known as whole genome duplication, is a major evolutionary force in plants, driving diversification and the generation of novel phenotypic variation, including superior abiotic and biotic stress tolerance. The enhanced stress resilience observed in certain polyploids is hypothesized to arise from dynamic epigenetic and genetic changes, including variations in gene content and cis-regulatory elements (CREs), that emerge following polyploidization. These changes directly impact various regulatory, signaling, and metabolic pathways associated with stress response and adaptation. Within polyploid populations, processes like gene duplications, fractionation, and homoeologous exchanges actively shape novel gene content variation, while, simultaneously, alterations in CREs (DNA sequences controlling gene expression) lead to diverse regulatory patterns. This dynamic interplay between changes in gene content and regulation further contributes to expanded phenotypic variation, including enhanced stress resilience. We discuss how advanced genomic and epigenomic techniques, such as pangenomics and single-cell assay for transposase-accessible chromatin with sequencing, are used to uncover these variations and outline new bioinformatic approaches to reveal the underlying genetics of stress resilience and adaptation. Finally, we summarize what remains poorly understood to guide future research, with the goal of unlocking the full potential for enhancing resilience in polyploid crops.